Effects of Self-Explanation on the Expansion and Indulgent of Mathematics Teaching: Case of the Students of the University of Wachemo - Abdela Atisso; Dawit Kachine; Dinku Feyissa (Qubahan Academic Journal)
The main goal of this study is to investigate the effects of self-explanation in improving proof comprehension in mathematics instruction: the case of Wachemo university undergraduate mathematics students of academic year 2020/2021. Moreover it is intended to find out interconnection between students achievement in mathematics and self-explanation in proof comprehension. To assess student’s self-explanation ability we applied self-explanation test and attitude test at the beginning and at the end to assess student’s character change to ward mathematics. In this study there are 48 students participated in both control and experimental groups. This study showed that the effectiveness of self-explanation in proof comprehension in mathematics courses. This also leading to recommend for curriculum developers to consider in self-explanation. One of the most strong findings of research is that conceptual indulgent is an important elements of expertise hence self-explanation is the tool to enhance students conceptual understanding, along with realistic knowledge and technical facility. The alliance of realistic knowledge, procedural expertise, and conceptual indulgent makes all three components operational in powerful ways. So that self-explanation has prominent effect in supporting students to achieve the intended objectives in proving theorems. Of these, two areas were measured quantitatively: student achievement in calculus and transformation geometry, and self-concept toward these courses. Those quantitative research findings are presented in chapter four with the details of the data collection procedures, the quantitative results, and an analysis of the outcomes.